High-stakes national testing, gender and school stress in Europe: A difference-in-difference analysis - Björn Högberg; Dániel Horn (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
Outcomes related to the wellbeing of students are increasingly being recognized as valuable objectives for education systems. In this study, we ask if high-stakes testing affects school-related stress among students and if there are gender differences in these effects. We combine macro-level data on high-stakes testing with survey data on more than 300,000 students aged 10-16 years in 31 European countries, from three waves (2002, 2006 and 2010) of the Health Behaviour in School-aged Children (HBSC) study. With variation in high-stakes testing across countries, years and grade levels, we use a quasi-experimental difference-in-differences (DD) design for identification of causal effects. We find that high-stakes testing increases self-reported school-related stress by almost 10 % of a standard deviation. This is primarily driven by a strong effect for girls, meaning that high-stakes testing increases the gender gap in school-related stress. The results are robust to a range of sensitivity analyses.
Keywords: I14; I21; I24; 330; high-stakes testing; stress; gender; quasi experiment